Effects of puerarin on the pharmacokinetics of astragaloside IV in rats and its potential mechanism - Huan Zhang; Jiaying Song; Huizhen Dai; Yanchao Liu; Lili Wang (Taylor & Francis Group, 2020)
Context Puerarin and astragaloside IV (AS-IV) are sometimes used together for the treatment of disease in Chinese clinics, however, the drug-drug interaction between puerarin and AS-IV is still unknown. Objective This study investigates the effects of puerarin on the pharmacokinetics of astragaloside IV in rats and clarifies its main mechanism. Materials and methods The pharmacokinetic profiles of oral administration of astragaloside IV (20 mg/kg) in Sprague-Dawley rats, with or without pre-treatment of puerarin (100 mg/kg/day for 7 days) were investigated. The effects of puerarin on the transport and metabolic stability of AS-IV were also investigated using Caco-2 cell transwell model and rat liver microsomes. Results The results showed that puerarin could significantly increase the peak plasma concentration (from 48.58 ± 7.26 to 72.71 ± 0.62 ng/mL), and decrease the oral clearance (from 47.5 ± 8.91 to 27.15 ± 9.27 L/h/kg) of AS-IV. The Caco-2 cell transwell experiments indicated that puerarin could decrease the efflux ratio of astragaloside IV from 1.89 to 1.26, and the intrinsic clearance rate of astragaloside IV was decreased by the pre-treatment with puerarin (34.8 ± 2.9 vs. 41.5 ± 3.8 μL/min/mg protein). Discussion and conclusions These results indicated that puerarin could significantly change the pharmacokinetic profiles of astragaloside IV, via increasing the absorption of astragaloside IV or inhibiting the metabolism of astragaloside IV in rats.